2014
DOI: 10.1111/pace.12523
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Cardiac Resynchronization Recipients: Association with Response and Impact on Outcome

Abstract: Clinical response, but not the echocardiographic one, was associated with improved QoL in CRT recipients. These preliminary data suggest that lack of improvement in QoL after CRT was associated with a strongly unfavorable prognosis, regardless of functional or echocardiographic response. Our results merit further studies with a larger number of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
1
5
0
2
Order By: Relevance
“…Subjects without QoL improvement were significantly more prone to experience MACE (61% vs. 32%) and die (44% vs. 18%) within the follow-up. Unimproved QoL increased the probability of future Major Adverse Cardiovascular Event (MACE) by 2.7 times and death by 3.2 times independently from clinical and echocardiographic response 22 . In our study, we showed similar outcome prediction with the simple and easy to obtain EQ-5D questionnaire in a larger group of traditional CRT patients.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Subjects without QoL improvement were significantly more prone to experience MACE (61% vs. 32%) and die (44% vs. 18%) within the follow-up. Unimproved QoL increased the probability of future Major Adverse Cardiovascular Event (MACE) by 2.7 times and death by 3.2 times independently from clinical and echocardiographic response 22 . In our study, we showed similar outcome prediction with the simple and easy to obtain EQ-5D questionnaire in a larger group of traditional CRT patients.…”
Section: Discussionsupporting
confidence: 69%
“…Recently, Lenarczyk et al 22 published the association of QoL with response and outcome in CRT-implanted patients. Ninety-seven participants of the Triple-Site vs. Standard Cardiac Resynchronization Therapy Trial (TRUST CRT) were included.…”
Section: Discussionmentioning
confidence: 99%
“…61 These factors and the broader concept of quality of life (QoL) are relevant since they have been associated with all-cause and cardiac-related mortality in patients with an ICD [62][63][64][65] and CRTD. 66,67 Several characteristics have been associated with poorer QoL and occurrence of anxiety/depression: ICD shock therapies, type D personality, non-CRT device, younger age and female gender. Females in particular, seem to express more anxiety (connected to procedure, shock, and death) and concerns for body image while depression seems to be equally expressed among the two sexes.…”
Section: The Effect Of Gender On Cied Implanting Techniquementioning
confidence: 99%
“…The PROSPECT (Predictors of Response to CRT) trial found that a five-point improvement on the KCCQ in the first 6 months of CRT was associated with a 15 % lower risk of all-cause mortality during 18 months of follow-up [ 4 ]. In accordance, a sub-study of the TRUST-CRT (Triple-Site versus Standard CRT) study showed that unimproved scores on the MLHFQ in the first 6 months of CRT decreased the probability of event-free survival by 2.2 times, independent of clinical and echocardiographic response [ 5 ]. In order to enhance risk stratification of heart failure patients indicated for CRT, it is important to know the prognostic value of patient-reported health status assessed prior to implantation.…”
Section: Introductionmentioning
confidence: 98%